Macrophage-epithelial interactions during influenza virus pneumonia : Alveolar recruitment pathways and impact on epithelial barrier integrity - Herold, Susanne Valerie; Justus Liebig University Giessen (My University, 2008)
Influenza A virus pneumonia is characterized by rapid progression to lung failure and high mortality. During early stages of infection significant amounts of leukocytes accumulate within the lung parenchyma including peripheral blood monocytes/macrophages, neutrophils and lymphocytes. Among these, macrophages have been attributed a crucial role in the host defense towards influenza virus (IV). In contrast, the precise transepithelial recruitment pathways of peripheral blood monocytes into the alveolar air space and the potential contribution of alveolarly accumulating ("exudate") macrophages to alveolar epithelial damage and lung barrier dysfunction during IV pneumonia has not yet been adequately addressed. Therefore, the present thesis investigated the chemokine-receptor involvement during IV-induced transepithelial monocyte migration in vitro and in vivo. Infection of primary murine alveolar epithelial cells with the mouse-adapted influenza A virus strain PR/8 markedly induced the release of the monocyte chemoattractants CCL2 and CCL5 followed by a strong monocyte transepithelial migration. This monocyte migratory response was strictly dependent on monocyte CCR2 but not CCR5 chemokine receptor expression. Moreover, using CCR2-deficient mice and function blocking anti-CCR2 antibodies in an IV pneumonia model, it was demonstrated that alveolar macrophage accumulation was solely dependent on monocyte-expressed CCR2 in vivo. In addition, the contribution of lung exudate macrophages to alveolar leakage formation during lethal IV pneumonia was delineated. Exudate macrophage accumulation in the lungs of PR/8 infected wildtype mice was associated with increased alveolar epithelial cell apoptosis, lung leakage and mortality. All these features of acute lung injury were strongly reduced in CCR2-/- mice and in wildtype mice treated with function blocking anti-CCR2 antibodies. Among several proapoptotic mediators analysed, TNF-related apoptosis-inducing ligand (TRAIL) gene expression was found to be markedly upregulated in alveolar exudate macrophages as compared to peripheral blood monocytes. Moreover, among the different alveolar recruited leukocyte subsets, TRAIL protein was predominantly expressed on macrophages. Finally, repetitive treatment of IV-infected mice with a monoclonal anti-TRAIL antibody resulted in significant reduction of alveolar epithelial cell apoptosis, attenuated alveolar leakage and significantly increased survival. Collectively, these findings demonstrate a major role of the CCL2/CCR2 axis in monocyte transepithelial migration. Additionally, CCR2-dependently recruited exudate macrophages were shown to be key players in the induction of alveolar leakage and mortality in influenza virus pneumonia, with macrophage TRAIL expression-linked epithelial apoptosis being recognized as major underlying mechanism and potential treatment target.

Die Influenza A Viruspneumonie verläuft häufig rasch progredient bis hin zum akuten Lungenversagen und ist gekennzeichnet durch eine hohe Mortalität. In den frühen Stadien der Infektion kommt es zu einer ausgeprägten Rekrutierung von Monozyten/Makrophagen, neutrophilen Granulozyten und Lymphozyten ins Lungenparenchym. Insbesondere den Makrophagen wird eine bedeutende Rolle in der Immunabwehr gegen das Influenzavirus (IV) zugeschrieben. Jedoch waren die molekularen Pfade der transepithelialen Rekrutierung peripherer Blutmonozyten in den Alveolarraum und die mögliche Rolle dieser alveolär akkumulierenden Makrophagen bei der Induktion des pulmonalen Epithelschadens mit Verlust der alveolären Barrierefunktion bei der Influenzapneumonie bis dato ungeklärt. In der vorgelegten Arbeit wurden die der IV-induzierten transepithelialen Monozytenrekrutierung zugrundeliegenden Chemokin-Rezeptor-Interaktionen in vitro und in vivo analysiert. Die Infektion primärer muriner Alveolarepithelzellen mit dem Maus-adaptierten Influenza A Virus PR/8 induzierte eine ausgeprägte Freisetzung der Monozyten-rekrutierenden Chemokine CCL2 und CCL5 und eine deutliche transepitheliale Migration peripherer Blutmonozyten. Diese war strikt abhängig von monozytär exprimiertem CCR2, nicht jedoch von CCR5. In einem IV-Pneumonie Modell konnte darüber hinaus anhand CCR2-defizienter Mäuse und mittels Applikation von anti-CCR2-Antikörpern gezeigt werden, dass die alveoläre Makrophagenrekrutierung auch in vivo primär durch monozytär exprimiertes CCR2 vermittelt ist. Zusätzlich wurde der Beitrag alveolär rekrutierter Makrophagen zum Verlust der alveolären Schrankenfunktion in der IV-Pneumonie untersucht. Die Akkumulation rekrutierter Makrophagen in der IV-infizierten Lunge von Wildtyp-Mäusen ging einher mit signifikant vermehrter Alveolarepithelzellapoptose, verstärkter alveolärer Leakage und höherer Mortalität im Vergleich zu CCR2-defizienten Mäusen oder anti-CCR2-vorbehandelten Tieren. Die Analyse der Genexpression verschiedener pro-apoptotischer Faktoren ergab eine signifikante Hochregulation des TNF-related apoptosis-inducing ligand (TRAIL) in alveolär rekrutierten Makrophagen im Vergleich zu peripheren Blutmonozyten IV-infizierter Tiere, wobei TRAIL ausschliesslich auf der Oberfläche alveolärer Makrophagen, nicht jedoch auf anderen alveolären Leukozytensubpopulationen exprimiert war. Schliesslich führte die repetitive Applikation eines monoklonalen anti-TRAIL-Antikörpers zu einer deutlichen Reduktion der alveolarepithelialen Apoptose, der alveolären Schrankenstörung und zum signifikant verbesserten Überleben IV-infizierter Tiere. In der vorgelegten Arbeit konnte die CCL2/CCR2-Achse als wichtigster Signalpfad bei der IV-induzierten transepithelialen Monozyten-/Makrophagenrekrutierung identifiziert werden. Darüber hinaus konnte gezeigt werden, dass CCR2-abhängig alveolär rekrutierte Makrophagen durch die Expression des pro-apoptotischen Faktors TRAIL eine Schlüsselrolle in der Induktion der alveolarepithelialen Apoptose und des Zusammenbruchs der alveolären Schranke übernehmen und dabei wesentlich zur Mortalität bei der Influenza Viruspneumonie beitragen.
Macrophagen-Epithel-Interaktionen bei Influenza-Pneumonie: Alveoläre Rekrutierungswege und Bedeutung für die epitheliale Barrierefunktion
Keywords: ARDS; Influenza; Makrophagen; Transmigration; Lungenödem; acute lung injury; influenza; macrophage; transmigration; alveolar leakage; ddc:610